Morality and Corruption Prevention - Singsuriya, Pagorn (Journal of Buddhist Studies Chulalongkorn University, 2024)
Morality is usually found as a component in measures proposed for corruption prevention. Underlying presuppositions are that corruption is opposite to morality, and moral cultivation leads to corruption prevention. However, these two presuppositions are problematic from the philosophical perspective. A conceptual analysis showed that, according to the mainstream view, morality is not a component of the concept of corruption. As a result, cases can be found in which moral persons commit corruption. The concept of immoral corruption, then, has to be considered in order to provide a framework for corruption prevention through morality.